Positionality Reloaded: Debating the Dimensions of Reflexivity in the Relationship Between Science and Society: An Editorial - Séverine Marguin; Juliane Haus; Anna Juliane Heinrich; Antje Kahl; Cornelia Schendzielorz; Ajit Singh (Historical Social Research, 2021)
It cannot be denied that reflexivity has become a must in social science methodological discourse in recent decades. The uses and functions of reflexivity in the research process have been well addressed historically, be it with regard to researchers' subjectivity, their perspectivity shaped by social origin and biographical life path, or their possible asymmetrical power relations with investigated actors. Nevertheless, we see an urgent need to discuss these issues. We claim that the practice of reflexivity, seriously shaken by the current transformation of (the understandings of) academic knowledge production, has become a challenging duty to fulfill. There is no straight and easy answer to the big questions of "for whom" and "for what purpose" do we produce "what kind of" knowledge and "how." Struggling for an appropriate positioning within global societal developments, we dedicate this special issue to the search for a critical, and the exploration of a lucid, (self-)reflection of academic research. In this respect, this special issue, 'Positionality Reloaded: Debating the Dimensions of Reflexivity in the Relationship Between Science and Society', sets out to explore how coexisting yet diverse conceptions of academic research and knowledge production can be reflexively considered and related to each other from an epistemological, ethico-normative, and ontological point of view.
Keywords: 300; reflexivity; positionality; methodology; methods; knowledge production; social sciences